Gender in the Music Industry: Rock, Discourse and Girl Power - Leonard, Marion (Routledge, 2017)
Why, despite the number of high profile female rock musicians, does rock continue to be understood as masculine? Why is rock generally assumed to be created and performed by men? Marion Leonard explores different representations of masculinity offered by, and performed through, rock music, and examines how female rock performers negotiate this gendering of rock as masculine. A major concern of the book is not specifically with men or with women performing rock, but with how notions of gender affect the everyday experiences of all rock musicians within the context of the music industry. Leonard addresses core issues relating to gender, rock and the music industry through a case study of 'female-centred' bands from the UK and US performing so called 'indie rock' from the 1990s to the present day. Using original interview material with both amateur and internationally renowned musicians, the book further addresses the fact that the voices of musicians have often been absent from music industry studies. Leonard's central aim is to progress from feminist scholarship that has documented and explored the experience of female musicians, to presenting an analytic discussion of gender and the music industry. In this way, the book engages directly with a number of under-researched areas: the impact of gender on the everyday life of performing musicians; gendered attitudes in music journalism, promotion and production; the responses and strategies developed by female performers; the feminist network riot grrrl and the succession of international festivals it inspired under the name of Ladyfest.

Rape and abuse: The music industry's dark side exposed (BBC News, 2017)
"Dangerous men" at the top of the industry are abusing their power, the BBC has been told.

Dick pics on blast: A woman’s resistance to online sexual harassment using humour, art and Instagram - Vitis, Laura; Gilmour, Fairleigh (Crime, Media, Culture, 2017)
This article brings to attention and explores women?s use of non-traditional forms of resistance to online sexual harassment. In this piece we use Anna Gensler?s Instagram art project Instagranniepants to examine how women are appropriating the language and practices of the cyber realm to expose online sexual harassment and to engender a creative resistance which is critical, comedic and entertaining. Drawing from interdisciplinary literature on witnessing, satire and shaming, we explore the techniques Gensler uses to not only document harassment but also resist, engage and punish those who seek to perpetrate it. This article problematises the stereotype of women as passive victims of online public spaces, and is critical of popular discourses that portray online spaces as exclusively risky and that position women as the natural victims of online violence. It concludes that a more nuanced account of women?s negotiation of online spaces is necessary, particularly as an overarching narrative of risk and victimisation undermines the liberatory potential of the online realm.
Keywords: Myriam; Résistance aux VACS

Not So Funny Business: Sexual Harassment in Stand-Up Comedy - Hansen, Briana (Workandmoney, 2017)
Up-and-coming Los Angeles comedian reflects on her experience of assault among some of the funniest people on the planet
Keywords: Sophie-Anne

ReadTheCode.ca - Canadian Creative Industries (2017)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

2192 women in the Swedish music industry behind appeal against sexism (Dagens Nyheter, 2017)
Sexual assault. Rude and outspoken sexism.

L'Union des artistes dépose des griefs pour harcèlement - Radio-Canada (Radio-Canada, 2017)
Après une vague de dénonciations de gestes à caractère sexuel dans le milieu artistique, l'Union des artistes (UDA) annonce avoir déposé des griefs pour harcèlement.
Keywords: Bibliographie; Nettoyer

Forty-Seven DJs, Four Women: Meritocracy, Talent, and Postfeminist Politics - Gadir, Tami (Dancecult, 2017)
In 2016, only four of forty-seven DJs booked for Musikkfest, a festival in Oslo, Norway, were women. Following this, a local DJ published an objection to this imbalance in a local arts and entertainment magazine. Her editorial provoked booking agents to defend their position on the grounds that they prioritise skill and talent when booking DJs, and by implication, that they do not prioritise equality. The booking agents’ responses, on social media and in interviews I conducted, highlight their perpetuation of a status quo in dance music cultures where men disproportionately dominate the role of DJing. Labour laws do not align with this cultural attitude: gender equality legislation in Norway’s recent history contrasts the postfeminist attitudes expressed by dance music’s cultural intermediaries such as DJs and booking agents. The Musikkfest case ultimately shows that gender politics in dance music cultures do not necessarily correspond to dance music’s historical associations with egalitarianism.

Un nouveau festival d'humour pour rire encore un peu, beaucoup, ensemble - Baillargeon, Stéphane (Le Devoir, 2017)
Un regroupement d’humoristes comprenant plusieurs têtes d’affiche du Québec crée le Festival du rire de Montréal. La première mouture du nouvel événement prendra l’affiche à l’été 2018, promettent les artistes.

Justice 2.0: Street harassment victims’ use of social media and online activism as sites of informal justice - Fileborn, Bianca (The British Journal of Criminology, 2017)
Emerging scholarship has considered the potential for online spaces to function as sites of informal justice. To date, there has been little consideration of the experiences of individuals who seek justice online, and the extent to which victims’ justice needs can be met online. Drawing on the findings of a mixed-methods research project with street harassment victims in Melbourne, Australia, I consider participants’ reasons for, and experiences of, disclosing their encounters of street harassment online. I examine the extent to which these ‘map on to’ a selection of victim’s justice needs. While it is evident that online spaces can function as sites of justice, it is vital to ask for whom and in which contexts justice can be achieved online.

Léa Clermont-Dion accuse Michel Venne de l’avoir agressée - Bussières, Ian; Piedboeuf, Guillaume (Le Soleil, 2017)
L’écrivaine et militante Léa Clermont-Dion, qui avait révélé en 2014 avoir été agressée sexuellement à l’âge de 17 ans, a déposé une plainte à la police contre le fondateur de l’Institut du Nouveau Monde, Michel Venne. Des allégations d’agression sexuelle que nie ce dernier.
Keywords: Bibliographie; Nettoyer

Michel Brûlé visé par une plainte d'agression sexuelle à Québec - Piedboeuf, Guillaume (La Tribune, 2017)
Une écrivaine de la Rive-Sud de Québec accuse l’éditeur Michel Brûlé de l’avoir agressée sexuellement à sa résidence du Vieux-Québec, en mars 2014, alors qu’elle venait lui proposer un manuscrit. Jill Côté a porté plainte à la police de Québec, vendredi, pour un incident dont M. Brûlé nie l’existence.
Keywords: Bibliographie; Nettoyer

Le patron des Éditions des Intouchables Michel Brûlé à son tour visé par des allégations d’inconduites sexuelles - Lévesque, Ève (Le Journal de Montréal, 2017)
Sept ex-employées se vident le cœur.
Keywords: Bibliographie; Nettoyer

Allégations de nature sexuelle: Gilbert Rozon visé par neuf femmes - Pineda, Améli (Le Devoir, 2017)
Neuf femmes racontent au «Devoir» ainsi qu’au 98,5 FM avoir été victimes de harcèlement et d’agressions sexuelles de la part du fondateur de Juste pour rire, Gilbert Rozon, et ce, dans la foulée du mouvement #MeToo. Certaines d'entre elles étaient même mineures au moment des incidents rapportés. Et pendant des années, elles ont cru être seules.
Keywords: Bibliographie; Nettoyer

Allégations de nature sexuelle: Gilbert Rozon visé par neuf femmes - Pineda, Améli (Le Devoir, 2017)
Neuf femmes racontent au «Devoir» ainsi qu’au 98,5 FM avoir été victimes de harcèlement et d’agressions sexuelles de la part du fondateur de Juste pour rire, Gilbert Rozon, et ce, dans la foulée du mouvement #MeToo. Certaines d'entre elles étaient même mineures au moment des incidents rapportés. Et pendant des années, elles ont cru être seules.

Inconduites sexuelles reprochées à Éric Salvail - Gagnon, Katia; Vallet, Stéphanie (La Presse, 2017)
Avances sexuelles en string, parties intimes exhibées ou empoignées, tentatives de séduction insistantes dans des salles de montage: 11 personnes ont raconté à La Presse avoir subi des inconduites, ou en avoir été témoins, de la part du producteur et animateur Éric Salvail, la plupart du temps dans un contexte professionnel.
Keywords: Bibliographie; Nettoyer

When Women Do Not Want It: Young Female Bargoers’ Experiences With and Responses to Sexual Harassment in Social Drinking Contexts - Graham, Kathryn; Bernards, Sharon; Abbey, Antonia; Dumas, Tara M.; Wells, Samantha (Violence Against Women, 2017)
Women frequently experience unwanted sexual touching and persistent advances at bars and parties. This study explored women?s responses to these unwanted experiences through online surveys completed by 153 female bargoers (aged 19-29) randomly recruited from a bar district. More than 75% had experienced sexual touching or persistence (46% both). Most women used multiple deterrent strategies, including evasion, facial expressions, direct refusals, aggression, friends? help, and leaving the premises. Women experienced negative feelings (disrespected, violated, disgusted, angry, embarrassed), especially from incidents involving touching. Cultural change is needed to reduce substantial negative impacts of sexual harassment on women in drinking and other settings.

Gender, Subjectivity, and Cultural Work: The Classical Music Profession - Scharff, Christina (Routledge, 2017)
What is it like to work as a classical musician today? How can we explain ongoing gender, racial, and class inequalities in the classical music profession? What happens when musicians become entrepreneurial and think of themselves as a product that needs to be sold and marketed? Gender, Subjectivity, and Cultural Work explores these and other questions by drawing on innovative, empirical research on the working lives of classical musicians in Germany and the UK. Indeed, Scharff examines a range of timely issues such as the gender, racial, and class inequalities that characterise the cultural and creative industries; the ways in which entrepreneurialism – as an ethos to work on and improve the self – is lived out; and the subjective experiences of precarious work in so-called ‘creative cities’. Thus, this book not only adds to our understanding of the working lives of artists and creatives, but also makes broader contributions by exploring how precarity, neoliberalism, and inequalities shape subjective experiences. Contributing to a range of contemporary debates around cultural work, Gender, Subjectivity, and Cultural Work will be of interest to scholars and students in the fields of Sociology, Gender and Cultural Studies.
Keywords: Music; Myriam; Social Science / General; Social Science / Sociology / General

Architects singer calls out man who sexually assaulted a fan: 'Not at my f***ing show' (The Independent, 2017)
Singer paused the show after witnessing the incident from the stage

Swedish music festival to go 'women-only' following string of sexual assaults - White, Adam (The Telegraph, 2017)
Sweden's biggest music festival will be replaced next year by a women-only alternative after reports of a series of rapes and sexual assaults at this year's event.
Keywords: Crime; Culture; Music; Skepta; Standard; Sweden

Data and responsibility: Towards a feminist methodology for producing historical data on women in the contemporary UK film industry - Cobb, Shelley; Wreyford, Natalie (Feminist Media Histories, 2017)
This paper addresses how feminist interrogations of research methods and knowledge claims have an important role to play in the collection and dispersion of quantitative data. Taking the contemporary film industry as a historical formation, and seeking to identify and understand patterns of continued gendered inequality, we consider the methodological and ethical dilemmas we have experienced as feminist researchers gathering and presenting quantitative data on the numbers of women working in the UK film industry between 2003 and 2015. We argue that data plays a paradoxical role in creating a sense of women’s absence and arrive at a set of guiding principles for feminist quantitative research in film histories.

Des musiciennes unies contre le sexisme - Lauzon, Véronique (La Presse, 2017)
Cent trente-cinq femmes issues du milieu musical ont décidé de dénoncer le sexisme et les injustices qu'elles subissent régulièrement au travail.
Keywords: Bibliographie; Nettoyer

Code of Silence (The Dance Current, 2017)
Fifteen years ago, Lisa, a dance conservatory student, became pregnant. She was told in no uncertain terms by her school’s directors that abortion was recommended, and that she wouldn’t be allowed to continue attending the conservatory otherwise. It was made clear to her that the fact that her pregnancy would be in its seventh month at the time of graduation...

Indian women journalists' responses to sexism and sexual harassment - Chadha, Kalyani; Steiner, Linda; Guha, Pallavi (International Communication Research Journal, 2017)
Gale Academic OneFile includes Indian women journalists' responses to sexism and by Kalyani Chadha, Linda Steiner, and Pall. Click to explore.
Keywords: Myriam; journalism

L'écrivain jeunesse Maxime Roussy en prison pour 5 ans - Nguyen, Michael (Le Journal de Montréal, 2017)
Pendant cinq ans, de 2006 à 2011, Roussy avait profité d’une jeune lectrice pour assouvir ses fantasmes sadomasochistes.
Keywords: Bibliographie; Nettoyer

The deterrent effects of Australian street-level drug law enforcement on illicit drug offending at outdoor music festivals - Hughes, Caitlin Elizabeth; Moxham-Hall, Vivienne; Ritter, Alison; Weatherburn, Don; MacCoun, Robert (International Journal of Drug Policy, 2017)
Background Australian and international street-level drug law enforcement deploy many strategies in efforts to prevent or deter illicit drug offending. Limited evidence of deterrence exists. This study assessed the likely impacts of four Australian policing strategies on the incidence and nature of drug use and supply at a common policing target: outdoor music festivals. Methods A purpose-built national online survey (the Drug Policing Survey) was constructed using five hypothetical experimental vignettes that took into account four policing strategies (High Visibility Policing, Riot Policing, Collaborative Policing, and policing with Drug Detection Dogs) and a counter-factual (no police presence). The survey was administered in late 2015 to 2115 people who regularly attend festivals. Participants were block-randomised to receive two vignettes and asked under each whether they would use, possess, purchase, give or sell illicit drugs. Results Compared to ‘no police presence’, any police presence led to a 4.6% point reduction in engagement in overall illicit drug offending: reducing in particular willingness to possess or carry drugs into a festival. However, it had minimal or counterproductive impacts on purchasing and supply. For example, given police presence, purchasing of drugs increased significantly within festival grounds. Offending impacts varied between the four policing strategies: Drug Detection Dogs most reduced drug possession but High Visibility Policing most reduced overall drug offending including supply. Multivariate logistic regression showed police presence was not the most significant predictor of offending decisions at festivals. ConclusionConclusion The findings suggest that street-level policing may deter some forms of drug offending at music festivals, but that most impacts will be small. Moreover, it may encourage some perverse impacts such as drug consumers opting to buy drugs within festival grounds rather than carry in their own. We use our findings to highlight trade-offs between the goals of public health promotion and crime control in street-level enforcement.
Keywords: Deterrence; Drug law enforcement; Supply; Use

Rape culture, lad culture and everyday sexism: researching, conceptualizing and politicizing new mediations of gender and sexual violence - Phipps, Alison; Ringrose, Jessica; Renold, Emma; Jackson, Carolyn (Journal of Gender Studies, 2017)
Introduction to Special Issue of Journal of Gender Studies entitled Rape culture, lad culture and everyday sexism: Researching, conceptualizing and politicizing new mediations of gender and sexual violence.

Skipping a beat: Assessing the state of gender equality in the Australian music industry - Cooper, Rae; Coles, Amanda; Hanna-Osborne, Sally (2017)
This report demonstrates that male advantage is a pervasive feature of the Australian music industry. Using publicly available published data the report interrogates the industry dynamics that have produced a contemporary music scene in which radio playlists, festival line-ups, industry awards, peak bodies and major industry boards are dominated by male contributions and voices. We make 5 key recommendations, discussed in more detail in the report, to begin the process of addressing the industry’s chronic gender inequality: 1. Collect more and better data on the music industry on a gender disaggregated basis; 2. Establish a well-resourced independent gender equality industry advocacy body; 3. Use gender equality criteria in deciding public funding outcomes; 4. Increase women’s representation in decision-making structures; 5. Address gender bias in the Australian music industry by prioritising inclusivity and representation as core industry values (for example through funding and implementing training programs). The music industry is skipping a beat when it comes to gender equality. We hope that our report will stimulate industry thinking and action for change.

The Going Out In Sydney App: Evaluating the Utility of a Smartphone App for Monitoring Real-World Illicit Drug Use and Police Encounters Among Festival and Club Goers - Hughes, Caitlin Elizabeth; Moxham-Hall, Vivienne Louisa (Substance Abuse: Research and Treatment, 2017)
Gaining accurate information on illicit drug use and policing in real-world settings is a challenge. This study examines the utility of a smartphone app (‘Going Out In Sydney’) to prospectively follow up illicit drug use and policing encounters at music festivals and licensed entertainment precincts in Sydney, Australia. In all, 38 regular festival and licensed entertainment venue attendees used the app to log nights out over a 3-month period, including (1) where they went (eg, festival, nightclub), (2) the prevalence of illicit drug use, and (3) the incidence and nature of police encounters. A survey and interview were then conducted about the utility of the app. The app enabled rich data collection (n = 353 entries) about illicit drug use and policing at both target settings. Follow-up surveys indicated that most participants were extremely satisfied with the ease of use of the app and privacy afforded, and compared with other data collection modes, such as paper-based logs and online surveys, rated the app the most desirable method of data collection. This suggests smartphone apps may be a viable option for future studies on illicit drug use and policing of drugs.
Keywords: Mobile app; app; drug use; offending; policing; smartphone

Not in our house Chicago Theatre Community (Not in our house Chicago Theatre Community, 2017)
making safe spaces to do dangerous work
Keywords: Bibliographie; Nettoyer

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
This article contextualizes some of the roles that women played in Montreal’s interwar jazz scene. The archives testify to the importance of pianists such as Vera Guilaroff and Ilene Bourne, piano teacher Daisy Peterson Sweeney, dance teachers Olga Spencer Foderingham and Ethel Bruneau, as well as black women performers on the variety stage in the development of Canada’s most thriving jazz scene in the first half of the twentieth century. This article explains why women were drawn to these particular performance spaces (piano, teaching, theatrical dance) and documents the historiographical processes that have led to their marginalization from the historical record.
Keywords: Bibliographie; Nettoyer

Montréal une ville festive pour toutes: Avis sur la sécurité des femmes et des jeunes femmes cisgenre et trans lors des événements extérieurs à Montréal - Conseil des Montréalaises (2017)
Keywords: Bibliographie; Camille; Nettoyer

More Than Two-Spirit: Queer Indigenous Sovereignty and Survivance in Museums - Cooper, Caitlin Skye (Université de Washington, 2017)
Keywords: Bibliographie; Nettoyer

gender inequalities in music: a comparative study of policy responses in the UK and Sweden - de Boise, S (International Journal of Cultural Policy, 2017)

Consultations publiques sur le harcèlement et la violence sexuelle en milieu de travail: ce que nous avons entendu - Emploi et Développpement social Canada (Gouvernement du Canada, 2017)
Keywords: Bibliographie; Nettoyer

‘Staff can't be the ones that play judge and jury’: Young adults’ suggestions for preventing unwanted sexual attention in pubs and clubs - Fileborn, Bianca (Australian & New Zealand Journal of Criminology, 2017)
This paper explores young adults' suggestions for preventing unwanted sexual attention in licensed venues. Despite emerging evidence that unwanted sexual attention and sexual violence are significant issues faced by young adults in the night-time economy, there has been little introduced in the way of preventative strategies or campaigns. Drawing on a mixed-methods research project undertaken in Melbourne, Australia, I contend that exploring young adults' suggestions for prevention is instructive in a number of ways. Young adults are the primary users of licensed venues and thus may provide insight into potential strategies for prevention. It can also illuminate the discursive positions that young adults draw on in talking about prevention and their understandings of unwanted sexual attention.
Keywords: Camille

Code of Silence: A call to action to address and prevent abuse in dance communities - Forcier, Marie France (The Dance Current, 2017)
Keywords: Bibliographie; Nettoyer

*Loi visant à prévenir et à combattre les violences à caractère sexuel dans les établissements d’enseignement supérieur - Gouvernement du Québec (RLRQ c P-22.1, 2017)
Keywords: Bibliographie; Nettoyer

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments' policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands' creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors influenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-specific research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change: Sexual harassment in the creative industries - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments’ policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands’ creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors inﬂuenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-speciﬁc research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.
Keywords: Bibliographie; Irina; Nettoyer

Debranchée (Unplugged) - Laurier, Mathilde; St-Laurent, Marie-Claude; Hébert, Maude; Milot, Marie-Ève (2017)
Débranchée (Unplugged) est une fiction qui traite des violences sexuelles dans le monde adolescent. La pièce raconte l'histoire de deux amies ébranlées par les rumeurs d'agressions sexuelles qui se propagent à haute vitesse dans leur école. Quand Allison brise la loi du silence, toute une chaîne de réactions s'enclenche. Des témoignages fusent, donnant une voix à toutes ces violences sexuelles trop souvent vécues dans l'anonymat. Devant l'ampleur du phénomène, les deux protagonistes cherchent à transformer l'explosion créée en un élan de solidarité. Elles iront jusqu'au bout. Le show aura lieu.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les dénonciations publiques d'agressions sexuelles : du mauvais usage de la présomption d’innocence - Lessard, Michaël (Revue Femmes et Droit, 2017)
French Abstract: Lorsqu’une victime dénonce son agresseur sur la place publique, certaines personnes tentent de la réduire au silence en invoquant le droit à la présomption d’innocence. Ce fut particulièrement évident en 2014, lors du mouvement #AgressionNonDénoncée ; ce le fut encore à l’automne 2015, alors que des femmes autochtones de Val-d’Or dénonçaient les agressions sexuelles commises à leur endroit par des policiers ; ce le fut aussi en 2016 à l’occasion de la dénonciation du député Gerry Sklavounos par Alice Paquet ; et l’argument légaliste réapparaît ainsi périodiquement sur la scène publique. Pourtant, peut-on vraiment bâillonner une victime en mettant de l’avant les droits de son agresseur ? L’auteur estime qu’il s’agit là d’un mauvais usage de la présomption d’innocence. Dans ce texte, il explique que la présomption d’innocence doit être replacée dans son contexte juridique. Le droit à la présomption d’innocence est un principe fondamental qui protège les accusés contre le pouvoir punitif de l’État. Il trouve uniquement application dans le processus pénal et n’est pas conçu pour être employé sur la scène publique. De plus, l’auteur explique que, dans le cadre du processus pénal, la présomption d’innocence favorise la création d’un espace de discussion où les parties peuvent débattre de la culpabilité. Pourtant, lorsqu’elle est invoquée sur la scène publique, elle ne fait que placer les victimes dans un processus violent de remise en question de leur crédibilité, tout en protégeant les agresseurs. Son invocation crée une atmosphère qui décourage les dénonciations. Le débat public dévie, laissant peu de place pour critiquer nos systèmes de plaintes dysfonctionnels et la culture du viol. En ce sens, la présomption d’innocence n’est pas invoquée afin d’établir un dialogue constructif, mais plutôt pour faire taire les critiques.English Abstract: When a victim reports her aggressor publicly, some people try to silence her voice under the guise of the right to the presumption of innocence. This was especially remarkable in 2014, within the movement #AgressionNonDénoncée; and again in the fall of 2015, when Val-d’Or Indigenous women reported being sexually assaulted by police. It was also the case in 2016 when Alice Paquet denounced Member of Provincial Parliament Gerry Sklavounos, and the legal argument thus periodically reappears on the public stage. However, can we really silence a victim by advancing the rights of her aggressor? The author believes that this is a case of inappropriate use of the presumption of innocence. In this text, he explains that the presumption of innocence must be placed in its legal context. The right to the presumption of innocence is a principle that protects litigants against the punitive power of the state. Its sole application belongs in the criminal process, and it was not designed to be used as such on the public stage. In addition, the author explains that, at the heart of the criminal process, the presumption of innocence promotes the creation of a discussion space where all parties may debate the guilt. However, when it is invoked in the public sphere, it only places the victims in an aggressive process of questioning their credibility while protecting the aggressors. Its invocation creates a climate that deters denunciations of sexual assaults. The public debate deviates, leaving little room to criticize our dysfunctional complaint systems and rape culture. In that sense, the presumption of innocence is not invoked in order to establish a constructive dialogue, but it has the effect of shutting down its critics. In this article, the author explains why the right to the presumption of innocence must not be engaged in this way in the public sphere.
Keywords: Bibliographie; Nettoyer

"They're Only Laughing 'Cause You're Pretty": Women's Experiences at Comedy Clubs - Lopez, Victoria Angelina (2017)
Stand-up comedy, like many forms of public entertainment or workplace organizations, is a field dominated by men. The deeply embedded perception that women are not funny, or not as funny as their counterparts, allow men’s privileged position in pursuing their career in comedy without their humor being questions based on their gender. However, the women’s’ experiences were found to be challenging with women’s humor being questioned and overshadowed by a hostile environment of sexual harassment. This disparity in the number of women represented in comedy is even more prevalent when it comes to the number of women who participate in stand-up comedy at the amateur level of open mic nights. This thesis examines gender disparity among comedians, the prejudices and discrimination women comedians face at the level of amateur comedian, and how they navigate through those barriers in comedy. Based on the findings from 14 in depth-interviews with 7 men and 7 women comedians, as well as observations of open-mic nights, this study investigates their experiences and perceptions of gender politics in comedy.
Keywords: Comedy clubs; Communication and the arts; Social sciences; Sophie-Anne

Sexual Harassment, Criminal Misconduct & Bullying in Australian Live Performance - Media Entertainment Arts Alliance (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

Our Music My Body: 2017 Campaign & Survey Report - OurMusicMyBody (2017)
Keywords: Bibliographie; Nettoyer

Preventing Sexual Harassment and Abuses of Power: A Code of Behaviour - Royal Court Theatre (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

Le traitement médiatique du mouvement #AgressionNonDénoncée dans la presse écrite québécoise francophone - Savard-Moisan, Raphaëlle (Université du Québec à Montréal, 2017)
Keywords: Bibliographie; Nettoyer